2015
DOI: 10.1002/joc.4433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boreal summer intraseasonal oscillation on rainfall extremes in southern China

Abstract: How boreal summer intraseasonal oscillation (BSISO) modulates the probability and spatial distributions of extreme rainfall occurrence over populous southern China was examined, using the newly proposed BSISO indices and two high‐resolution rain‐gauge‐based rainfall datasets in China. The probability density function of May–August rainfall in southern China is skewed towards large values in phases 2–4 of the first component and in phases 5–7 of the second component of BSISO life cycle, during which the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 42 publications
(58 reference statements)
2
106
0
1
Order By: Relevance
“…The BSISO influences on precipitation in the Yangtze River Valley are fulfilled via modulating the position of the western Pacific subtropical high (Ren et al 2013;Lu et al 2014). Precipitation extremes also show close relationship with two BSISO components (Hsu et al 2016;Gao et al 2016). For instance, both Lu et al (2014) and Zhu et al (2003) revealed that floods in the Yangtze River Basin during 1998 were in tandem with the active phase of 30-60-day BSISO.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The BSISO influences on precipitation in the Yangtze River Valley are fulfilled via modulating the position of the western Pacific subtropical high (Ren et al 2013;Lu et al 2014). Precipitation extremes also show close relationship with two BSISO components (Hsu et al 2016;Gao et al 2016). For instance, both Lu et al (2014) and Zhu et al (2003) revealed that floods in the Yangtze River Basin during 1998 were in tandem with the active phase of 30-60-day BSISO.…”
Section: Introductionmentioning
confidence: 94%
“…Before being released, this dataset went through rigorous quality control procedures by the Climate Data Center (CDC) of the National Meteorological Information Center (data and documents available online http://cdc.cma.gov.cn/home.do), China Meteorological Administration (CMA). Extreme precipitation and extreme high temperature mainly concentrate during the period from May to August in southern parts of China, due to influences of East Asian summer monsoon (Ding and Chan 2005;Hsu et al 2016). So May-August is selected as the study period.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the BSISO on precipitation in China has been described for specific regions and for individual rainfall events (e.g. Yang and Li 2003;Zhu et al 2003;Mao et al 2010;Gao et al 2013;Liu et al 2014;Li et al 2015;Hsu et al 2016). Previous studies have also linked subseasonal wintertime precipitation variability to the MJO (Liu and Yang 2010;Jia et al 2011;He et al 2011).…”
Section: Introductionmentioning
confidence: 99%